Modified Reptile Search Optimization Based Analysis of Inventory Framework With Interval-Valued Inventory Expenses - Sharma, Yogesh; Kushwaha, Anurag; Krishnamoorthy, Manju Bargavi Sankar; Singhal, Priyank (International Journal of Intelligent Systems and Applications in Engineering, 2023)
This study presents an inventory model that incorporates interval-valued inventory expenses and the effect of pre-payment (PP). The PP is a fixed proportion of the cycle’s total procurement expense; this results in a discount on procurement expense but a loss of interest on the PP. It is assumed that the inventory expenses, including ordering, purchase, shortage, and carrying expenses, are interval-valued. We examine two scenarios: one with no shortages and the other allowing for partially backlogged deficiencies. Due to loyal customers and some customers transferring shops, the demand rate is projected to fall over a limited interval in the second case. Both cases use interval arithmetic to design mixed integer restricted optimization issues with interval targets. We proposed a Modified Reptile Search Optimization (MRSO) algorithm to tackle these issues. The suggested model is demonstrated numerically, and sensitivity analysis are carried out to determine the effects of various inventory factors on optimal profit. The inventory model with interval-valued (IV) expenses can be solved most effectively using the MRSO method. The results emphasize PP, IV expenses, and shortage cases in inventory management. The model and MRSO algorithms assist decision-makers in improving their inventory strategies and optimizing profitability under uncertain expense and demand conditions.